Structure of an elective course in physical education «winter football» using figital technologies - Kapilevich L.V. ,; Ilyin A.A. ,; Wang Ya. ,; Li T. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify the pedagogical technology of teaching students of specialized groups in winter football. Methods and structure of the study. The basis of the study was the analysis of educational, training and competitive gaming activities. Results and conclusions. It is shown that the pedagogical technology for teaching students of specialized winter football groups should be a set of pre-designed effective and interconnected components of the educational process. It is advisable to include elements of phygital technologies in up to 20% of training time; they can be aimed primarily at developing coordination abilities, reaction time and team interactions.